Fertilizantes de liberação controlada no crescimento e desenvolvimento do mamoeiro 'THB' - Simão, Letícia Abreu (2017)
Brazil is one of the main producers and exporters of papaya. The main Brazilian states producing papaya are Bahia and Espírito Santo, which are responsible for about 60% of the national production. The controlled release fertilizer use is rarely used field in the state of Espírito Santo, especially for fruit trees. In the State, it has been applied in the eucalyptus crop. The use of these types of fertilizers has as one of the main advantages the reduction of labor for cover fertilizations. In these fertilizers, the release of nutrients is dependent on the granule size, temperature and humidity. The nutrients are made available by hydrolysis and by the action of microorganisms. The objective of this study was to evaluate the efficiency of controlled release fertilizers on growth and development of plants papaya 'THB' in the vegetative and productive stage using fertilizers Basacote P-MAX 6M (Formula 17- 43-00)® , Basacote NK-MAX 9M (Formula 17-43-00)® and DuraTec Top 14 (Formula 14-07-14)® . The experiment was carried out between June 2015 and November 2016, in the field, at the Santa Terezinha farm, Caliman Agrícola S. A., in Linhares, Espírito Santo state. It adopted the random block design with six replicates and five treatments. The treatments consisted of the application of doses of 25, 50, 75 and 100 g cova-1 of controlled release fertilizers Basacote P-MAX 6M® in the planting and ix a control that was the drip fertigation. In the production phase, treatments consisted of cover fertilization by applying two controlled release fertilizers, Basacote NK-MAX 9M® and Duratec Top 14® , at 3, 6, 9 and 12 months after planting. They were evaluated at flowering stem diameter (SD), the first flower insertion height, plant height (PH), leaf petiole length, number of leaves per plant and percentage of pit defined for sex; in the production phase it was evaluated SD, PH, number of marketable fruits, fruit mass, soluble solids and inner fruit firmness at 8, 13 and 17 months after planting; productivity was assessed by cumulative production, from 8 to 17 months. The new technology package is an alternative to fertigation, and Basacote P-MAX 6M® controlled release fertilizer can be applied to 25 g cova-1 at planting, and cover fertilization with Basacote NK-MAX 9M® and Duratec Top 14® after 90 days of planting.